corporate Social Legal Responsibility and Customer Loyalty: A Survey of Telecommunication Firms in Hochiminh City, Vietnam - Minh, Ngo Ngoc; Loc, Nguyen Duc (International Journal of Psychosocial Rehabilitation, 2020)
Corporate social responsibility (CSR) has been used by many companies to gain public confidence through providing essential commodities of some high value to a customer. The study objective was to determine the effect of legal responsibility on customer loyalty. Carroll model and Stakeholder theory were used to explore empirical study. The paper targeted all customers of telecommunication companies in Hochiminh City-the biggest city in Vietnam. Stratified sampling was used to group the population while the systematic sampling technique was used to obtain 955 customers. A structured questionnaire was used for data collection. The reliability of the questionnaire was checked using Cronbach Alpha test. Data collected were coded and analyzed using both descriptive and inferential statistics. The results indicated that CSR legal initiatives positively impact on customer loyalty. Therefore, telecommunication firms should engage in CSR in order to create a positive attitude on their customers to enhance loyalty.